Workshop Response Time at the Emergency Room Lubuk Pakam Health Center - Ramadhan Ritonga, Rahmad; Kurata’ain, Kurata’ain (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Higher level of achievement of the community in the local area, this is also a service in the area which is a world-class public and individual service, at the same time prioritized in promotion and prevention efforts. Decree of the Minister of Health Number 129 of 2008 concerning Minimum Service Standards in Emergency Installations, Response Time, also known as